Determinan Perilaku Konsumen Melalui Aktivitas Sosial Media Marketing dan Electronic Word of Mouth - Wahono, Johannes Widjaja; Wedyarsa, Maria Josefina Amita; Fakhirah, Farah (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Purpose– This study aims to investigate social media marketing activities and electronic word of mouth (EWOM) on consumer behavior (purchase intention and loyalty intention) through quality relationships.Methodology – This study used a quantitative approach, where the source of data used was primary data in the form of questionnaires. The distribution of questionnaires is carried out online. Respondents in this study amounted to 108 respondents, where respondents were individuals who had shopped using social media. The sampling technique uses purposive sampling. The analytical tool used is the structural equation model, and is tested using PLS-SEM.Findings – This research shows that social media activities have an effect on relationship quality, but electronic word of mouth has no effect. In addition, the results of this study show that relationship quality mediates the influence of social media activities and EWOM on customer behavior (purchase intention and loyalty intention).Originality/Novelty – The findings of this study can provide a reference for the Company to carry out social media marketing and EWOM activities intensely in order to improve the quality of the relationship between producers and consumers, which in turn will increase consumer buying interest.Implications – The practical implication of this research is that companies can be more intense in carrying out activities with social media. This is because doing so can improve